1998
DOI: 10.1111/j.0435-3676.1998.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Sublimation of ice through sediment in beacon valley, antarctica

Abstract: The time-dependent physics of ice sublimation through thin layers of till is considered, to determine whether sublimation could be sufficiently slow to permit the preservation of ice for 8 Ma in the Dry Valleys, Antarctica. This could only happen if the ice had been very thick, but other evidence (crystal size, dating of other ice-cored moraines) is not consistent with this possibility. Steady-state models suggest that sublimation is rate-controlled by vapor transport. A time-dependent model coupling vapor con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 11 publications
5
92
3
Order By: Relevance
“…This value is in good agreement with modeled ice sublimation rates of the order of 0.1 mm a À1 in various regions in the McMurdo Dry Valleys (e.g. Beacon Valley and Linneaus Terrace, Hindmarsh et al, 1998;McKay et al, 1998;Schorghofer, 2005). A much lower sublimation rate, 0.017 mm a À1 , was found for Beacon Valley by Kowalewski (2006), but this may well be an underestimate because it is based on climate data that do not include January, the period of most rapid sublimation as inferred from data in Victoria Valley (Hagedorn et al, 2007).…”
Section: Introductionsupporting
confidence: 85%
“…This value is in good agreement with modeled ice sublimation rates of the order of 0.1 mm a À1 in various regions in the McMurdo Dry Valleys (e.g. Beacon Valley and Linneaus Terrace, Hindmarsh et al, 1998;McKay et al, 1998;Schorghofer, 2005). A much lower sublimation rate, 0.017 mm a À1 , was found for Beacon Valley by Kowalewski (2006), but this may well be an underestimate because it is based on climate data that do not include January, the period of most rapid sublimation as inferred from data in Victoria Valley (Hagedorn et al, 2007).…”
Section: Introductionsupporting
confidence: 85%
“…The significance of this buried ice is that if it is of Miocene age (minimum 8.1 Ma BP) -as has been inferred from stratigraphic relationships to overlying tills dated by 40 Ar/ 39 Ar analyses of presumed in situ volcanic ash -it confirms the persistence of a cold, hyper-arid climate in the area throughout the Pliocene and refutes the notion of an unstable East Antarctic Ice Sheet during this period (Sugden et al, 1995). The ability of ice in the near subsurface to survive sublimation over the time spans proposed has been questioned (Hindmarsh et al, 1998), as has the interpretation that the volcanic ash deposits are undisturbed and thus provide a chronological constraint on the age of the ice. Through an analysis of the concentrations of cosmogenic 3 He and 21 Ne in two surface dolerite erratics and one shielded erratic from within the ice, Schäfer et al (2000) demonstrated that sublimation rates could not have exceed more than a few metres per million years and that the ice must be at least several million years old.…”
Section: Burial Events a Sediment Burialsupporting
confidence: 51%
“…Sublimation and erosion rates are probably not steady on yearly timescales, and are likely punctuated by extreme events and periods of stability, but over ~10 5 years, these variations are indistinguishable from steady degradation. The development of a sublimation till over dirty ice is thought to shield the underlying ice from sublimation, and as the till layer thickens, sublimation rates should lower (Hindmarsh et al, 1998;Schorghofer, 2005;Kowalewski et al, 2006). The results of this study suggest that erosion of the overlying sublimation till may act to thin the till such that sublimation rates remain constant on a ~10 5 year timescale.…”
Section: Discussionmentioning
confidence: 73%
“…The results of this study suggest that erosion of the overlying sublimation till may act to thin the till such that sublimation rates remain constant on a ~10 5 year timescale. The age and stability of the relict glacier ice in Beacon Valley has been the subject of much debate and research (Sugden et al, 1995;van der Wateren and Hindmarsh, 1995;Hindmarsh et al, 1998;Marchant et al, 2002;Ng et al, 2005;Kowalewski et al, 2006). The results of this study only record what has happened at the study sites for the past 0·4-2 Ma, and therefore do not directly address the preservation of ice that is 8·1 Ma.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation